2023
DOI: 10.1101/2023.01.23.525199
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Streamlined regulation of chloroplast development in the liverwort Marchantia polymorpha

Abstract: Photosynthesis in eukaryotic cells takes place in specialised plastids. The regulation of plastid development is crucial for multicellular systems such as plants. Two families of transcription factors known as Golden2-like (GLK) and GATA regulate plant chloroplast development, and the miR171-targeted SCARECROW-LIKE (SCL) GRAS transcription factors regulate chlorophyll biosynthesis. The extent to which these proteins carry out conserved roles in non-seed plants such as the liverworts is not known. Here we deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 93 publications
(260 reference statements)
0
12
0
Order By: Relevance
“…24,25 Taking advantage of the rapid and predominantly haploid life-cycle we used M. polymorpha as a testbed for each of these candidates and subjected each to CRISPR/Cas9-mediated editing. With the exception of MpGLK, which has previously been reported to lead to a pale phenotype when mutated 15 only one other candidate had low chlorophyll. This was Mp5g11830, annotated as MpRR-MYB5 in the M. polymorpha genome database, but previously also referred to as a CIRCADIAN CLOCK ASSOCIATED1-like RR-MYB-Related transcription factor.…”
Section: Mprr-myb5 Regulates Chloroplast Development Synergistically ...mentioning
confidence: 93%
See 1 more Smart Citation
“…24,25 Taking advantage of the rapid and predominantly haploid life-cycle we used M. polymorpha as a testbed for each of these candidates and subjected each to CRISPR/Cas9-mediated editing. With the exception of MpGLK, which has previously been reported to lead to a pale phenotype when mutated 15 only one other candidate had low chlorophyll. This was Mp5g11830, annotated as MpRR-MYB5 in the M. polymorpha genome database, but previously also referred to as a CIRCADIAN CLOCK ASSOCIATED1-like RR-MYB-Related transcription factor.…”
Section: Mprr-myb5 Regulates Chloroplast Development Synergistically ...mentioning
confidence: 93%
“…Two of these (MpGLK, MpGATA4) are homologs of known photosynthesis regulators in A. thaliana 10,21 and MpGLK has a confirmed role in M. polymorpha. 15 The remainder included a number of B-BOX (BBX) domain proteins known to interact with the master regulator of photomorphogenesis HY5 22 , a homeobox-leucine zipper (HD-ZIP) protein ATHB17 whose ortholog in A. thaliana regulates photosynthesis-associated nuclear genes in response to abiotic stress, 23 a C2H2 type zinc finger transcription factor with unknown function in A. thaliana, and a MYB-related gene predicted to regulate photosynthesis gene expression. 24,25 Taking advantage of the rapid and predominantly haploid life-cycle we used M. polymorpha as a testbed for each of these candidates and subjected each to CRISPR/Cas9-mediated editing.…”
Section: Mprr-myb5 Regulates Chloroplast Development Synergistically ...mentioning
confidence: 99%
“…Chlamydomonas reinhardtii , Chlorella spp , Micromonas commoda , Volvox , Ostreococcus ). However, the detection of GLK orthologs in Zygnematophyceae green algae (Yelina et al, 2023), and a potential GLK that lacks the GCT box in the Charophyceae Chara braunii , a green algae with a complex body, support that their emergence predates the land colonisation. To investigate the evolutionary history of GLKs, we identified GLK orthologs covering a wide range of photosynthetic lineages using currently available sequenced genomes and transcriptomes from public databases (Table S1, Dataset S2).…”
Section: Maize Golden2 and The Glk Familymentioning
confidence: 99%
“…Due to GLKs' specific function as regulators of chloroplast development (Table 1) (e.g. Fitter et al, 2002; Powell et al, 2012; Yasumura et al, 2005; Yelina et al, 2023), it is not surprising that GLKs were not found in the parasitic plant Sapria himalayana (Van Bel et al, 2022), which has lost the plastid genome and nuclear genes involved in chloroplast function (Cai et al, 2021). Our dataset, which includes more lineages and diversity than previous characterisations of the GLK family, supports the conclusion that GLK gene number is not associated with photosynthetic type, but more likely with regulation (Figure 2 a, b), as suggested by Wang et al (2013).…”
Section: Maize Golden2 and The Glk Familymentioning
confidence: 99%
“…We hypothesized that transcriptional regulation of photosynthesis is largely conserved. The transcription factors GOLDEN2-LIKE (GLK) were originally identified in Z. mays and shown to control photosynthetic transcripts in the monocot Z. mays , the dicot A. thaliana , and the liverwort Marchantia polymorpha (Fitter et al, 2002; Yasumura et al, 2005; Yelina et al, 2023) already demonstrating a large degree of conservation. The species under investigation operate different modes of photosynthesis.…”
Section: Introductionmentioning
confidence: 99%